Le Tao-Tö King comme source poétique de Henry Bauchau ? Essai de génétique littéraire - Rampone, Debora (Ponti/Ponts, 2024)
The publication in 1991 of the tale Diotime et les lions, which previously was a part of the novel OEdipe sur la route, captured the interest from several researchers of Henry Bauchau’s literary production. Especially interesting for our researches are the studies involving the origin of the character of Diotime and the cultural influences inspiring this story. Nevertheless, due also to the detailed reading of the author’s published diaries (in particular Jour après jour and Dernier journal) we had the opportunity to observe the paucity of further investigations pertaining to the manifest influence of Taoist philosophy in Diotime et les lions. For this reason, our investigation, based on a selection of diaristic extracts, attempts to chronologically retrace the phases leading the writer to include Laozi’s figure concealed in the figure of the Vieillard-Enfant. Subsequently, we aimed to bring to light this issue in Diotime et les lions through a reflection focused mainly on the last pages of the story and the reading of the book of the Tao Te Ching ascribed to Laozi.